Study of Multi-layered Cobalt Silicide Nanostructured Thin Films Prepared by Ion Beam Sputtering - Kaur, Karamjit; Kumar, Anil (Current Nanomaterials, 2022)
Aim: This work focuses on the different existing techniques for synthesis of nanomaterials, the selection of potential process for preparation of Co/Si and Co/Si/Co such that material with optimum characteristics may be obtained. Background: The process of synthesis plays a crucial role in physical properties and associated phenomena acquired by them, and hence is a deciding factor in various potential applications of the materials. Objective: The aim of the study was to investigate the properties of multi-layered cobalt silicide nanostructured thin films prepared by ion beam sputtering. Method: The cobalt silicide is selected for synthesis using IBS technique owing to vast scope of its application in manufacturing microelectronic devices. Result: The formation of nanostructured layers has been confirmed through XRD and XRR patterns. Conclusion: The role of substrate thickness, interface quality and crystalline structure is very important in deciding properties of multilayer nano-structured thin films.
Keywords: nano-structured thin films